Protein for athletes: A practical guide - Zachwieja, J.
Protein is an essential part of an athlete`s diet and as a sports health professional, chances are you`re fielding questions about protein from your athletes on a daily basis. With so much new information and research emerging, making the right recommendations can be challenging.